Effect of applied stress on corrosion properties of Q235 steel with multi-layer epoxy coating. Issue 1 (1st January 2023) - Zhang, Ruixiang; Dong, Yuguo; Liu, Ling; Qu, Xingdong; Liu, Feng; Wang, Yang; Peng, Longgui; Du, Lifei
Abstract: Organic coating is one of the most effective, economical and universal methods for corrosion resistance of metal at a small, but the stability of the coating is highly dependent on the applied stress. In the study, a comprehensive experiment was conducted to investigate the corrosion progress of Q235 steel sheets in 3.5% NaCl solution and 10% H2 SO4 . The effect of applied stress on the corrosion as well as the corresponding adhesion characteristics of Q235 steel are examined and quantitatively analyzed. Results indicate that, compared with the NaCl solution, the H2 SO4 solution has aggressive corrosion on the Q235 steel sheets, and the corrosion would be largely aggravated with increasing applied stress. Additionally, the decreased adhesion grade of the epoxy coating is a synergic result of the immersion time and the stress, and the continuous dissolution of the coating would lead to the aggravation of corrosion, which side-fact indicates that the prepared epoxy resin paint could show efficient anti-corrosive properties. Therefore, the stress has a direct influence on the adhesion ability of the prepared epoxy resin coating, which would decrease the anti-corrosion properties of the coating.